GLOBALISASI DAN ANCAMANNYA BAGI KETAHANAN NASIONAL DALAM ASPEK IDEOLOGI - Titra Gunawijaya; I Made Gami Sandi Untara (Veda Jyotih: Jurnal Agama dan Sains, 2023)
Globalization as a phase of change carried out by people in various parts of the world, in which countries, regions, and communities are connected to each other in various fields. The blurring of geographical boundaries is the hallmark of globalization, this encourages wider information exchange. This paper discusses the threat of globalization that affects national resilience on ideological aspects using the Ethnography Content Analysis (ECA) method. The ease of access to information was also used by terrorist groups to spread radical ideologies using the pretext of the struggle to defend religion. They recruit their Muslims and make religion a protective shield. At this level, terrorist groups have become a threat to national resilience, because its existence can threaten the safety of the community through bombing actions carried out in various places. Besides, this group has also infused people with a radical ideology that has disrupted the country’s sovereignty with their desire to uphold Islamic law in Indonesia.